Answer:
-2
Step-by-step explanation:
Let's call the number x. The statement tells us that
x^2 - 10 = 3x, or
x^2-3x-10 = 0
Factoring:
(x-5)(x+2) = 0. Here, we see that there are two solutions: x = 5 and x = -2. So, the negative solution is x = -2.
Answer:
the answer will be 5.
Step-by-step explanation:
Answer:
15 candles
Step-by-step explanation:
132.72÷8.4=15.8
therefore jerod can make 15 whole candles
hope this helps
Answer:
Since g(x) = f(2x), this means we substitute 2x in place of x for f(x):
g(x) = f(2x) = (2x)² = 4x²
Graphing this, the parabola is not moved from the parent graph f(x) = x², but the graph is compressed horizontally by a factor of 4.Step-by-step explanation: